Hybrid analysis method for US-based consumer product stocks during volatile market conditions - Chen, Ruokun (Nanyang Technological University, 2023)
The stock market is volatile. It is a mix of factors, events, numbers, and trends. During periods of volatility, it is no trivial matter to analyse stocks. There are three main analysis methods. Fundamental analysis focuses on the underlying business to identify sound long-term investments. Technical analysis focuses on the actions of market participants to identify buying and selling opportunities. News analysis focuses on events that affect individual companies and the entire stock market. This project explores the effectiveness of each method in the analysis of consumer product stocks listed on the New York Stock Exchange. Using fundamental analysis, we devised a process to separate companies by their performance. Then, a few selected companies are analysed using technical analysis and news analysis to understand how market factors and events can affect their price movements. Back tests of stock portfolios showed promising results in generating excess return relative to the US stock market. Results in this paper highlighted the superior performance of combined analysis over single analysis methods for consumer sector stocks